2018
DOI: 10.1007/s10608-018-9897-6
|View full text |Cite
|
Sign up to set email alerts
|

Youth Cognitive-Behavioral Depression Prevention: Testing Theory in a Randomized Controlled Trial

Abstract: This study tested the plausibility of a theoretical model of change for the Penn Resiliency Program (PRP), a cognitive-behavioral (CB) depression prevention program for adolescents. Middle school students (N = 697) were randomized to PRP, an assessment-only control condition (CON), or a placebo-control condition (PLA). Explanatory style and depressive symptoms were evaluated over 24 months of follow-up. Relative to both CON and PLA, there were significant indirect effects of PRP on 12-month levels of depressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…Although there are studies with depressed adults investigating the association between CBT skill use and depressive symptom change (e.g., Hawley et al, 2017; Jarrett, Vittengl, Clark, & Thase, 2011, 2013; Strunk, Hollars, Adler, Goldstein, & Braun, 2014; Webb, Beard, Kertz, Hsu, & Björgvinsson, 2016), no study has tested the extent to which depressed adolescents acquire cognitive and behavioral skills in CBT and, critically, whether these skills predict symptom change. Although not focused on treatment, related research on cognitive-behavioral depression prevention programs suggests that their beneficial effects may, in part, be mediated by the acquisition of cognitive–behavioral skills (Brunwasser, Freres, & Gillham, 2018).…”
mentioning
confidence: 99%
“…Although there are studies with depressed adults investigating the association between CBT skill use and depressive symptom change (e.g., Hawley et al, 2017; Jarrett, Vittengl, Clark, & Thase, 2011, 2013; Strunk, Hollars, Adler, Goldstein, & Braun, 2014; Webb, Beard, Kertz, Hsu, & Björgvinsson, 2016), no study has tested the extent to which depressed adolescents acquire cognitive and behavioral skills in CBT and, critically, whether these skills predict symptom change. Although not focused on treatment, related research on cognitive-behavioral depression prevention programs suggests that their beneficial effects may, in part, be mediated by the acquisition of cognitive–behavioral skills (Brunwasser, Freres, & Gillham, 2018).…”
mentioning
confidence: 99%
“…Negative styles of thinking such as pessimistic or hopeless explanatory styles predicts depression (Lakdawalla et al, 2007 ) and interventions that modify pessimistic explanatory style and other negative thinking styles have effects on depression (e.g., Horowitz and Garber, 2006 ). Furthermore, some studies have found initial evidence suggesting that improvement in explanatory style mediates intervention effect on depressive symptoms in children (Yu and Seligman, 2002 ; Brunwasser et al, 2018 ). In depression, a reduction in cognitive negative thoughts, especially perfectionism, has been found to be an important mediator among depressed adolescents (Stice et al, 2010 ).…”
Section: Mediators Related To the Components In The Echo Studymentioning
confidence: 99%
“…Substantial and sustained efforts have been made over many decades to develop and evaluate evidence-based treatment for depression in children and adolescence ( 18 ). Besides treatment, researchers have also investigated programs and initiatives designed to prevent depression onset in children and adolescents ( 19 22 ). When implementing a prevention program, it is critical to identify the sources of heterogeneity in intervention effects and to attempt to bolster the impact of interventions.…”
Section: Introductionmentioning
confidence: 99%